VALUES OF ISLAMIC EDUCATION IN THE BOOK "TURNING DEFEAT INTO VICTORY LEARNING FROM THE UHUD WAR" BY HEPI ANDI BASTONI - Mahira, Nazza; Hidayat, Rahmat; Aqsho, Muhammad (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2024)
This research method is library research. The Aims of this research are: (1) To find out what the values of Islamic education contained in the book Changing Defeat into Victory are learned from the Battle of Uhud by Hepi Andi Bastoni, (2) To find out how the construction of Islamic educational values contained in the book Changing Defeat into Victory Learning from the Uhud War by Hepi Andi Bastoni, (3) To find out how The implications of the values of Islamic education contained in the book Changing Defeat into Victory Learning from the Battle of Uhud by Hepi Andi Bastoni with current educational practices.The results showed that The values of Islamic education contained in the book Turning Defeat into Victory Learning from the Uhud War are: : (a) Values of Faith education consist of (i) Faith in Allah SWT, (ii) Faith in Angels, (iii) Faith in the Prophet and Messenger, (iv) Belief in the Last Day, (v) Belief in Qada and Qadar. (b) Values of Moral Education consist of (i) Trust, (ii) Love, (iii) Sincerity, (iv) Tawakal, (v) Patience, (vi) Deliberation, (vii) Courage, (viii) Keep promises, (ix) Please help and (x) Tolerance. And (c) Worship Education Values consist of (a) Mahdah Worship, namely Prayer and (b) Ghairu Mahdah Worship, namely praying.